Cold adaptation of the Antarctic archaeon, Methanococcoides burtonii assessed by proteomics using ICAT - Goodchild, A.; Raftery, M.; Saunders, N. F. W.; Guilhaus, M.; Cavicchioli, R. (Journal of Proteome Research, 2005)
Using isotope coded affinity tag (ICAT) chromatography and liquid chromatography-mass spectrometry, 163 proteins were identified from the cold-adapted archaeon, Methanococcoides burtonii. 14 proteins were differentially expressed during growth at 4 degrees C and 23 degrees C. Knowledge of protein abundance, protein identity and gene arrangement was used to determine mechanisms of cold adaptation. Growth temperature was found to affect proteins involved in energy generation and biosynthesis linked to methanogenesis, membrane transport, transcription and protein folding, as well as affecting the expression of two hypothetical proteins. Pooling the data from this ICAT study with data from a previous two-dimensional gel electrophoresis study highlighted consistencies and differences between the two methods, and led us to conclude that the two approaches were generally complementary. This is the first report of ICAT applied to Archaea, or for the study of cold adaptation in any organism.